The Effect of Antimicrobial Extract on The Characteristics of Tomatoes Coated by Edible Coating based on Tapioca Flour - Rispiandi; Fitria Yulistiani; Adela Putri Nurarofah; Fadila Isra Azzahra (Fluida, 2023)
The edible coating is a food coating material inhibitor of transpiration and respiration. Layer is not fully effective in preventing food spoilage. The spoilage process can occur more quickly if fruit with high moisture content has infected. The research aimed to determine optimum concentration of antimicrobial extract in maintaining shelf life and shrinkage of tomatoes, dominant bacteria in fruit spoilage, between Escherichia coli or staphylococcus. Figure out antimicrobial extracts that are effective in preventing microbial growth. Research begins with the extraction process, testing the active compounds in the extract, combining edible coatings and white turmeric and bitter melon extract with concentrations of 0%, 2.5%, 5%, 10%, 20%, 30%, and 100 respectively), tomato fruit coating. The tests included shelf life, weight loss, best antimicrobial extract, and inhibition diameter. The results more concentration of the extract made the shelf life longer to 14 days and reduced shrinkage by 3.53%. Secondary metabolite compounds in the form of saponins, steroids, and triterpenoids. The minimum concentration of 30% bitter melon and white turmeric extract to prevent bacterial activity and the diameter of the inhibition zone in the range of 10-12 mm showed the extract had the moderate ability. The more dominant bacteria in tomato fruit rot is Staphylococcus aureus.